2022
DOI: 10.3390/nu14081677
|View full text |Cite
|
Sign up to set email alerts
|

Nuts and Metabolic Syndrome: Reducing the Burden of Metabolic Syndrome in Menopause

Abstract: Menopause imposes a dramatic fall in estrogens, which is followed by an increase in the proportion of fat. The rising androgen/estrogen ratio along the menopause transition favors the accumulation of central fat, which contributes to insulin resistance and a series of concatenated effects, leading to a higher incidence of metabolic syndrome. The modulatory effect of diet on the metabolic syndrome phenotype has been shown for the Mediterranean diet, and nuts are key determinants of these health benefits. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…One of the major metabolic changes during menopause is insulin resistance, which leads to the development of diabetes mellitus [6,7]. This association has been widely reported in clinical studies, showing that menopause is associated with an increased risk of impaired glucose tolerance, elevated blood pressure, and elevated triglycerides [8][9][10]. In animal models, ovariectomy resulted in increased gluconeogenesis and decreased glycogen levels in the liver, uterus, skeletal muscle, and myocardium [11].…”
Section: Introductionmentioning
confidence: 94%
“…One of the major metabolic changes during menopause is insulin resistance, which leads to the development of diabetes mellitus [6,7]. This association has been widely reported in clinical studies, showing that menopause is associated with an increased risk of impaired glucose tolerance, elevated blood pressure, and elevated triglycerides [8][9][10]. In animal models, ovariectomy resulted in increased gluconeogenesis and decreased glycogen levels in the liver, uterus, skeletal muscle, and myocardium [11].…”
Section: Introductionmentioning
confidence: 94%
“…In an in vivo study, a leaf extract demonstrated the ability to increase resistance to viral infections as well as to provide an immunostimulant effect in humans and animals (increasing interferon production and natural MAP-30's antiviral activity was also relative to the herpes virus in vitro. It contains three anti-HIV proteins: alpha-and beta momorcharin, and MAP-30, and charantin, beta-DSitosterl-beta-D-glucoside, 5,25-Stigmastadien-3-beta-Dglucoside, serotonin, and many kinds of amino acids [56][57] . Anti HIV activity: Bitter melon has also been suggested as a treatment for AIDS, but the evidence thus far is too weak to even mention.…”
Section: Isolation Of Charantinmentioning
confidence: 99%
“…Due to poor nutrition and a lack of physical activity, MS has become a global epidemic in recent decades ( Lim et al, 2008 ). MS has attracted attention due to its worldwide incidence and high correlation with diabetes and cardiovascular disease ( Gluvic et al, 2017 ; Bauset et al, 2022 ). MS appears to have a minimal risk factor; however, it may not only cause numerous complications but also increase the morbidity and mortality of numerous chronic diseases ( Ford, 2005 ).…”
Section: Introductionmentioning
confidence: 99%